2009
DOI: 10.1113/expphysiol.2008.044651
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a prior high‐intensity knee‐extension exercise on muscle recruitment and energy cost: a combined local and global investigation in humans

Abstract: The effects of a priming exercise bout on both muscle energy production and the pattern of muscle fibre recruitment during a subsequent exercise bout are poorly understood. The purpose of the present study was to determine whether a prior exercise bout which is known to increase O 2 supply and to induce a residual acidosis could alter energy cost and muscle fibre recruitment during a subsequent heavy-intensity knee-extension exercise. Fifteen healthy subjects performed two 6 min bouts of heavy exercise separat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 70 publications
2
41
1
2
Order By: Relevance
“…Therefore, the progressive decrease in MdPF from the onset of LL might reflect the appearance of fatigue in the muscle fibres that were already active in the priming high-intensity leg exercise. Additionally, it has been suggested that priming high-intensity leg exercise alters and/or increases the muscle fibre recruitment of the subsequent exercise (Burnley et al 2002;Fukuba et al 2002;Layec et al 2009). This is in line with the higher slope of the iEMG/W and _ VO 2 /W-relationship below the GET in the present study.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Therefore, the progressive decrease in MdPF from the onset of LL might reflect the appearance of fatigue in the muscle fibres that were already active in the priming high-intensity leg exercise. Additionally, it has been suggested that priming high-intensity leg exercise alters and/or increases the muscle fibre recruitment of the subsequent exercise (Burnley et al 2002;Fukuba et al 2002;Layec et al 2009). This is in line with the higher slope of the iEMG/W and _ VO 2 /W-relationship below the GET in the present study.…”
Section: Discussionmentioning
confidence: 98%
“…The Bohr effect will have a systemic effect due to the establishment of a metabolic acidosis (and an increase in core temperature), and will be elicited by both the priming leg and arm exercise. However, during the ramp exercise following the priming leg exercise, it can be suggested that sequential recruitment of motor units consisting of different fibre types (Henneman 1985) will be disturbed as a consequence of muscle fatigue from the previous high-intensity leg exercise (Burnley et al 2002;Krustrup et al 2004;Layec et al 2009). Priming highintensity leg exercise has shown to increase the motor unit recruitment in subsequent exercise (Layec et al 2009) and according to the size principle (Henneman 1985) the additional muscle fibres that will be recruited are likely to be fasttwitch fibres with a different C (a-v) O 2 profile (Ferreira et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Subjects performed three consecutive trials of sustained isometric contraction (60% of MVC) until exhaustion, defined as the inability to maintain the force level within 10% of target force for 5 s. Such tasks, comprised of consecutive submaximal contractions, are known to enhance the effects of fatigue, such as energy cost and motor unit recruitment (Layec et al, 2009;Vollestad, Wesche, & Sejersted, 1990). Subjects were given 15 s of rest between trials.…”
Section: Fatigue Taskmentioning
confidence: 99%
“…A recent study demonstrated the usefulness of the combination of NIRS with nuclear magnetic resonance (NMR) techniques for obtaining robust information regarding muscle oxidative metabolism and haemodynamics [19].…”
Section: (C) Advanced Near-infrared Imaging Technologies and Multi-momentioning
confidence: 99%
“…erector spinae, intercostal, multifidus, paravertebral, serratus anterior) were also investigated during cycling, back extension and bending forward. So far, NIRS has been applied for studying exercise-induced muscle damage [11,20], ergonomics/biomechanics [21], heterogeneity of muscle O 2 supply/demand [12,22], muscle activation [11,23], priming exercise [19,24], respiratory muscle blood flow/fatigue [25,26], the role of the brain in muscle fatigue [27,28], the time course of oxidative metabolism [6,29] and the effect of exercise training [30]. Owing to the restriction of the allocated space, this review article neglects an in-depth discussion of the 160 studies published in the last four years.…”
Section: Main Fields Of Near-infrared Spectroscopy Applications For Smentioning
confidence: 99%